Impact of Climate Change on Apple Cultivation and Socio-Political Crisis in Northern Himalaya of India - Sujit Sarkar; R.N. Padaria (Indian Journal of Extension Education, 2018)
The study was conducted with the objective of assessing the impact of climate change on farmers’ livelihood in the Himalayan ecosystems of India. All the farmers (100%) agreed that apple production had declined in the area and shifted upwards. Increased incidence of diseases like canker, scab etc. in apple was reported by 84 percentage farmers. The study revealed that all the farmers (100%) unanimously reported decreased snowfall in the area. Forty two per cent farmers from Shimla reported more increase in temperature in winter season than summer season. A little less than three-fourth (73%) farmers reported delayed rainfall and 47 per cent reported decreased snowfall. The illegal occupation of forest land in high altitude by the apple growers led into socio-political (37%) crisis in the region. Just less than half of the respondents (45%) reported about decline in plant species like Deodar (Cedrus deodara), Kail (Pinus Wallichiana) etc., resulted in ecological crisis in the region.